Nondestructive Optical Inspection System for the Dicing Street Quality of Copper/Low-k Wafer - Lin, Sheng-Feng; Chen, Cheng-Huan; Lo, Cheng-Yao (My University, 2015)
To resolve the issue in detecting sidewall crack defect mode in the die singulation of copper/low-k wafer after laser pre-groove/cleaning process, we combine a dedicated optical system with automatic optical inspection system in the production line for the nondestructive wafer-by-wafer optical inspection system to inspect the dicing street quality of copper/low-k wafer. Experiment shows that the sidewall crack defect can be clearly identified with the proposed inspection system and it is potentially applicable for the production line.
Keywords: nondestructive optical inspection; sidewall crack; scattering; copper/low-k wafer